GUIDELINES FOR MEASURING BODY PARAMETERS FOR THE SELECTION OF A WHEELCHAIR FOR INDIVIDUALS WITH SPINAL CORD INJURY (Physical Culture and Sport: Scientific Perspective, 2025)
Wheelchairs are one of the most important assistive mobility devices for individuals with spinal cord injuries, as they directly influence independence, social integration, and quality of life. In the current conditions of Ukraine, characterised by both the consequences of military actions and limited resources in the healthcare system, there is a considerable shortage of access to properly fitted wheelchairs. Many users are provided with devices that do not correspond to their anthropometric parameters, functional abilities, or environmental requirements. This results in reduced comfort, inefficient use, secondary health complications, and a shortened service life of the wheelchair. Therefore, the implementation of international approaches, particularly the recommendations of the International Society of Wheelchair Professionals (ISWP) and the World Health Organization (WHO), becomes critically important for the optimisation of wheelchair provision in Ukraine.The article analyses the WHO four-step model of assistive device provision, which consists of assessment, selection, fitting/adjustment, and user training. Special emphasis is placed on the methodology of anthropometric measurements, which serves as the foundation of the assessment stage. Detailed attention is given to measurement techniques for pelvic width, thigh length, lower leg length, and back height. These parameters are crucial for ensuring proper biomechanics, ergonomic positioning, and functional mobility of the user. The study also addresses the risks of neglecting precise measurements, including the development of pressure ulcers, postural deformities, and limitations in daily activities.Furthermore, the article highlights the necessity of adapting international wheelchair fitting methods to the Ukrainian context. Such adaptation will contribute to increased efficiency, safety, and durability of wheelchairs while also supporting the user’s independence and participation in society. Another essential component is the preparation of qualified professionals capable of conducting systematic assessment, selection, and fitting of wheelchairs. The development of training programmes and educational infrastructure is identified as a strategic priority.In conclusion, the paper outlines prospects for future research, which include the creation of unified national protocols for wheelchair assessment and fitting, analysis of specific needs among different categories of users, and improvement of the professional training system. These steps are expected to establish a sustainable framework for high-quality wheelchair provision in Ukraine and ensure better integration of people with spinal cord injuries into everyday life.
Keywords: assistive mobility devices; assistive rehabilitation devices; wheelchair; physical therapy; spinal cord injury; provision; independence; process; participation